Microbubbles and Ultrasound Accelerated Thrombolysis for Peripheral Arterial Occlusions: The Outcomes of a Single Arm Phase II Trial. (September 2021) - Doelare, Sabrina A.N.; Jean Pierre, Dayanara M.; Nederhoed, Johanna H.; Smorenburg, Stefan P.M.; Lely, Rutger J.; Jongkind, Vincent; Hoksbergen, Arjan W.J.; Ebben, Harm P.; Yeung, Kak K.; ,; Wisselink, Willem; van der Meijs, Bram B.; et al.
Abstract : Objective: Acute peripheral arterial occlusions can be treated by catheter directed thrombolysis (CDT). However, CDT is time consuming and accompanied by the risk of bleeding complications. The addition of contrast enhanced ultrasound and microbubbles could improve thrombus susceptibility to thrombolytic agents and potentially shorten treatment time with a lowered risk of bleeding complications. This article reports the outcomes of the safety and feasibility of this novel technique. Methods: In this single arm phase II trial, 20 patients with acute lower limb ischaemia received CDT combined with an intravenous infusion of microbubbles and locally applied ultrasound during the first hour of standard intra-arterial thrombolytic therapy. The primary endpoint was safety, i.e., occurrence of serious adverse events (haemorrhagic complications and/or amputation) and death within one year. Secondary endpoints included angiographic and clinical success, thrombolysis duration, additional interventions, conversion, and quality of life. Results: The study included 20 patients (16 men; median age 68.0 years; range, 50.0 – 83.0; and 40% native artery and 60% bypass graft). In all patients, the use of microbubble contrast enhanced sonothrombolysis could be applied successfully. There were no serious adverse events related to the experimental treatment. Duplex examination showed flow distal from the occlusion after 23.1 hours (range 3.1 – 46.5) with a median thrombolysis time of 47.5 hours (range 6.0 – 81.0). The short term ABI and pain scores significantly improved; however, no changes were observed before or after thrombolysis in the microcirculation. Overall mortality and amputation rates were both 2% within one year. The one year patency rate was 55%. Conclusion: Treatment of patients with acute peripheral arterial occlusions with contrast enhanced sonothrombolysis is feasible and safe to perform in patients. Further research is necessary to investigate the superiority of this new treatment over standard treatment.